"The Impact of the COSO Internal Control Framework on Reducing Cybersecurity Risks: A Field Study of Banks in Sana’a, Yemen:" (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study examines the impact of the COSO Internal Control Framework on mitigating cybersecurity risks in banks operating in the Republic of Yemen. The study adopts a descriptive–analytical approach due to its suitability for the research objectives. Primary data were collected through a questionnaire administered to financial managers, internal audit managers, and employees working in financial management, internal auditing, and information technology departments. A total of 154 valid responses were analysed.The findings reveal a statistically significant impact of implementing the COSO framework on reducing cybersecurity risks in Yemeni banks. Specifically, a strong control environment, effective risk assessment, and well-designed control activities enhance banks’ ability to address cyber threats and minimize system vulnerabilities. The results also emphasize the critical role of information and communication, as well as continuous monitoring, in strengthening responses to cyberattacks and ensuring compliance with relevant standards and regulations.